PERSYARATAN LAHAN TANAMAN PORANG (Amarphopallus ancophillus) - Bambang Siswanto; Hidayati Karamina (Universitas Tribhuwana Tunggadewi, 2016)
Porang is a commodity crops are included in the family Araceae and the bush plants (herbs) with a single bulb in the ground. Porang grow in the forest because it requires only 50-60 percent of solar radiation. Porang can grow well in organic soil and dry soils with pH 6-7. For the purposes of the development porang required information about land suitability map. One of the constraints in preparing the land suitability map porang, is the unavailability of land requirements porang. Currently available is a land requirement of iles-iles. The purpose of this study was to develop land requirements porang, in order to work in the land suitability evaluation porang no longer use land requirements iles-iles. The research location is KPH Nganjuk region. The research was conducted in January to May 2012. The primary data obtained from field observation, while secondary data obtained from the literature, maps, and interviews with farmers and Perum Perhutani KPH Nganjuk employee. At every SPL was observed physical condition and taking soil samples.Not all parameters of land requirements Iles - iles can be used to evaluate the suitability of Porang. Parameter requirements Iles - iles that can be used to evaluate the Porang is coarse material, CEC, salinity, erosion, flood hazards, land preparation, dry months, C-organic. Proposed requirements for crop land porang as shown in Appendix 1